Ulasan Ilmiah: Peran ATP Dalam Rigor Mortis Kerang-Kerangan - Rina Heldiyanti; Ni Wayan Putu Meikapasa (Universitas Bumigora, 2023)
Shellfish are the Bivalvia Group which is one of the source of animal protein. After harvested, all fishery products, including shellfish, experienced rigor mortis which is an indicator of quality changes. Rigor mortis affect the texture of shellfish and caused the softening due to the activity of proteolytic enzymes. This review aims to provide information, of how Adenosine Triphosphate (ATP) plays a major role in changing the postharvest quality of shellfish and how to maintain its postharvest quality. Based on the literature study, it was found that rigor mortis is a process in which fishery products lose their flexibility due to increased muscle tension and correlates with a decrease in ATP. The degradation of ATP components begins 6 hours after harvest, especially in high temperature. In general, shellfish becomes soft quickly during storage which indicates damage. The harvest process and storage conditions influence postmortem changes. Various types of cooling systems have been widely used to preserve shellfish at temperatures of -4 to 0℃: cold storage, ice water, shaved ice, dry ice and ozone-shaved ice combinations. Shelf life can be extended by storage at sub-zero temperatures. Storage temperature can limit softening by reducing protease activity. Cooling temperatures can be advantageous in maintaining freshness and suppressing the growth of harmful microbes.